George Mason papers - Mason, George, 1725-1792.; Mason, George William, 1791-1855.; Mason, John, 1766-1849.; Mason, Thomson Francis, 1785-1838.
Container 1 and oversize container consist of copies and originals of correspondence, legal documents, land surveys, indentures, genealogy records, and financial records of George Mason and other family members including his son John Mason and grandsons George William Mason and Thomson Francis Mason. Documents John Mason's partnership in the merchant firm Mason, Fenwick and Company and his association with the Potowmack Canal Company (Potomac Canal Company). Also includes material pertaining to Thomson Francis Mason's activities with the Alexandria Canal Company and the Chesapeake and Ohio Canal Company.
Container 2 consists of correspondence, proposed amendments and resolutions, and other papers documenting Mason's role as a Virginia delegate to the federal constitutional convention in Philadelphia, Pa., in 1787, and the subsequent Virginia ratifying convention in 1788. Includes an early draft of the Virginia Declaration of Rights prepared by Mason and Thomas Ludwell Lee in 1776 for the Virginia state constitution; Mason's letters addressed to Martin Cockburn, Edmund Randolph, and his sons George Mason (1753-1796) and John Mason; and letters from Richard Henry Lee. Also contains a copy of Mason's letter to the "Committee of London Merchants," written in 1766, regarding the issue of taxation in the colonies.
Container 2 available only on microfilm
Microfilm edition of John Mason's correspondence available
A portion of the George Mason family papers available only on microfilm
Microfilm (nos. 10,113 & 11,105) produced from originals in the Manuscript Division.
Microfilm (no. 14,898) produced from originals in private hands.
Plantation owner and statesman.
Keywords: Cockburn, Martin -- Correspondence; Lee, Richard Henry, -- 1732-1794 -- Correspondence; Lee, Thomas Ludwell, -- 1730-1778.; Mason, George, -- 1753-1796 -- Correspondence; Randolph, Edmund, -- 1753-1813 -- Correspondence; Mason family; United States. -- Constitutional Convention -- (1787); Virginia. -- Convention -- (1788); Virginia; Alexandria Canal Company; Chesapeake and Ohio Canal Company; Mason, Fenwick and Company; Potomac Canal Company; Constitutional history -- United States; Constitutional history -- Virginia; Taxation -- United States; Great Britain -- Colonies -- Administration; Great Britain -- Colonies -- America; United States -- History -- Colonial period, ca. 1600-1775.; United States -- History -- 1783-1815.; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1789.; Virginia -- History -- Colonial period, ca. 1600-1775.; Virginia -- History -- 1775-1865.; Virginia -- Politics and government -- 1775-1865.; Plantation owners; Statesmen